Teaching and interpreting the Old Testament in Africa : written word, archaeology and oral world - Le Roux, Magdel (Old Testament essays, 2012)
In Africa we are confronted daily with a society that has lost its moral fibre, resulting in seemingly endless problems in the educational sector. Universities have the special task of promoting the humanities and applying social values and the social relevance in their teaching, which should lead to effective learning and an improvement in the quality of learning. Neither the written text (Hebrew Bible) nor the archaeological discoveries have provided us with sufficient information on certain Israelite practices and customs. Africa has traditions that need to be respected. A study of oral traditions may provide a supplementary, or perhaps alternate, view. A comparative study between Lemba and proto-Israelite customs and beliefs indicates that there is yet another group whose customs and rituals correspond to a great extent with those of the proto-Israelites. It is comparison in aid of cross-cultural interpretation, as is now forcefully stated in more recent studies in religion.